All-Solid-State High-Voltage Supercapacitors Using an Ionic Plastic Crystal-Based Electrolyte - Yoshizawa-Fujita, Masahiro; Kubota, Satoshi; Ishimoto, Shuichi (Frontiers in Energy Research, 2022)
Recently, ionic plastic crystals (IPCs) have been actively investigated to develop all-solid-state rechargeable batteries, such as lithium-ion batteries. Herein, we report supercapacitors assembled with mesoporous carbon electrodes and an IPC electrolyte, N-ethyl-N-methylpyrrolidinium bis(fluorosulfonyl)amide ([C2mpyr][FSA]). [C2mpyr][FSA] with a 10 mol% lithium bis(fluorosulfonyl)amide (LiFSA) dopant was used as the solid electrolyte in the supercapacitors. The charge–discharge tests of the supercapacitors were performed at various C-rates in the voltage range of 0–2.5 V at 25 °C. The capacitance of the cells was 12.3 F g-1 at a lower C rate (1 C = 8.9 mA g-1). The capacitance retention of the supercapacitors was maintained at approximately 100% up to 20 C, which was comparable to that of the cells containing organic electrolyte solutions. The advantage of using solid electrolytes was the fabrication of bipolar cells using two pairs of mesoporous carbon electrodes and a [C2mpyr][FSA]/LiFSA composite. The charge–discharge tests of the bipolar cells were also performed in the voltage range of 0–5.0 V at 25 °C. The capacitance of the bipolar cells was 6.4 F g-1 at a lower C rate. The bipolar cells exhibited a typical charge–discharge profile for 1000 cycles, confirming their stable cyclic performance. Thus, IPC electrolytes are interesting materials for developing all-solid-state high-voltage supercapacitors.